2020
DOI: 10.1371/journal.pone.0231860
|View full text |Cite
|
Sign up to set email alerts
|

Influence of back support shape in wheelchairs offering pelvic support on asymmetrical sitting posture and pressure points during reaching tasks in stroke patients

Abstract: Many poststroke hemiplegic patients have an asymmetrical wheelchair-sitting posture. This study aimed to investigate the impact of different back support shapes on asymmetrical sitting posture and pressure points among poststroke hemiplegic patients during an activities of daily living-related reaching task. This study included 23 poststroke hemiplegic patients who performed tasks that involved the movement of objects using the unaffected upper limb to the affected side while sitting in a conventional wheelcha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…However, in lateral flexion, the hemiplegic side showed a larger value than the non-hemiplegic side. The asymmetrical sitting posture of patients with stroke should be considered when determining ROM measurements [39]. In addition, the stiffness and spasticity of the trunk muscles on the hemiplegic side could limit lateral flexion to the non-hemiplegic side [40].…”
Section: Discussionmentioning
confidence: 99%
“…However, in lateral flexion, the hemiplegic side showed a larger value than the non-hemiplegic side. The asymmetrical sitting posture of patients with stroke should be considered when determining ROM measurements [39]. In addition, the stiffness and spasticity of the trunk muscles on the hemiplegic side could limit lateral flexion to the non-hemiplegic side [40].…”
Section: Discussionmentioning
confidence: 99%
“…Fujita et al 8 ) reported that increasing the thickness of the rear part of the seat cushion provided posterior pelvic support and could suppress posterior pelvic tilt. Ukita et al 9 ) stated that adjusting the shape of the back support could improve asymmetry in individuals with hemiparesis. Nagata 10 ) examined the effect of anterior knee support on sitting posture stability in severely disabled children.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the laboratory environment there are tools capable of quantifying the posture control. These are usually devices of high economic cost and with difficult accessibility in the daily clinic, although they are very reliable and sensitive (i.e., posturography and inertial measurement units) [ 12 , 13 ]. Taking into account this reality, the evaluation of neurological patients with a high degree of dependence is even more problematic, since, even if there are force platforms, electronic gateways, or inertial devices that can quantify the quality of their postural control, these people cannot stand on their own, which is usually the minimum requirement for these devices to perform measurements [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%